(untitled) (Altre Modernità, 2024)
Siegmund Ginzberg, Colazione a Pechino – Sogni e incubi di un impero senza tempo (Milano, Feltrinelli, 2022, 352 pp. ISBN 978-88-07-11158-7) di Francesco Michael Scaringella